A113 ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY IN PATIENTS WITH SURGICALLY ALTERED ANATOMY IN A CANADIAN TERTIARY REFERRAL CENTRE. (21st February 2022) - Motomura, D; Gan, S; Byrne, M; Donnellan, F
Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) has become a mainstay of diagnosis and treatment of pancreatobiliary conditions. Surgically altered anatomy presents unique challenges in the procedure, necessitating creative solutions such as different types of endoscopes and tools. Distinct from regular anatomy, forward viewing scopes are often required for successful cannulation and therapy of the pancreaticobiliary system. To our knowledge, there is limited data on the practice of ERCP in altered anatomy in Canada. Aims: Our aim is to present outcomes from a large series of patients with surgically altered anatomy who underwent ERCP at a large Canadian referral centre. Methods: All ERCP procedures at a tertiary referral centre in Vancouver, Canada from Oct 2020 to Oct 2021 were reviewed retrospectively. Inclusion criteria required surgically altered anatomy and attempted ERCP. Liver transplant patients with duct-to-duct anastomosis were not included in the series. Patients with incomplete procedure documentation were excluded. Demographic, procedural and outcome data were collected. Results are presented descriptively and as median + IQR for quantitative data. Procedural success was defined as cannulation and performance of a cholangiogram and/or pancreatogram Results: A total of 34 procedures met the inclusion criteria during the study period. Twenty-four procedures were on male patients (71%). Nineteen patients (56%) had had previous ERCP. Sixteen patients (47%) had choledocholithasis as the indication for the procedure, 9 patients (26%) had cholangitis and 5 patients (15%) had concerns of neoplasia. Some patients had multiple indications. Seventeen patients (50%) had roux-en-Y anatomy, 8 patients (24%) were post Whipple's and 6 patients (18%) had Billroth II type anatomy. Other altered anatomy included duodenal switch, and post gastrojejunostomy bypass. The most commonly used endoscope was the adult or pediatric colonoscope (74% of cases). Single balloon enteroscope was used in 5 cases (15%). Overall success rate was 74%. The breakdown of success rate by anatomy is shown in Table 1. One (3%) complication was noted in the form of mild cholangitis, requiring only outpatient antibiotics. Conclusions: Experience in ERCP in patients with altered anatomy is becoming more pertinent in tertiary care. Cannulation and therapy is more difficult in this cohort, but still successful in the majority of cases. Adverse events remain uncommon. Knowledge of forward viewing ERCP techniques is critical in surgically altered anatomy. Future studies will aim to expand the retrospective cohort for more quantitative analysis. Funding Agencies: None